A regional ionospheric TEC mapping technique over China and adjacent areas on the basis of data assimilation. Issue 6 (8th June 2015) - Aa, Ercha; Huang, Wengeng; Yu, Shimei; Liu, Siqing; Shi, Liqin; Gong, Jiancun; Chen, Yanhong; Shen, Hua
Abstract: In this paper, a regional total electron content (TEC) mapping technique over China and adjacent areas (70°E–140°E and 15°N–55°N) is developed on the basis of a Kalman filter data assimilation scheme driven by Global Navigation Satellite Systems (GNSS) data from the Crustal Movement Observation Network of China and International GNSS Service. The regional TEC maps can be generated accordingly with the spatial and temporal resolution being 1°×1° and 5 min, respectively. The accuracy and quality of the TEC mapping technique have been validated through the comparison with GNSS observations, the International Reference Ionosphere model values, the global ionosphere maps from Center for Orbit Determination of Europe, and the Massachusetts Institute of Technology Automated Processing of GPS TEC data from Madrigal database. The verification results indicate that great systematic improvements can be obtained when data are assimilated into the background model, which demonstrates the effectiveness of this technique in providing accurate regional specification of the ionospheric TEC over China and adjacent areas. Key Points: Kalman filter data assimilation scheme driven by GNSS data Generating TEC regional maps over China and adjacent areas